Long walk to freedom - Mandela, Nelson (London Abacus, 2013)
The riveting memoirs of the outstanding moral and political leader of our time, Long Walk to Freedom brilliantly recreates the drama of the experiences that helped shape Nelson Mandela's destiny. Emotive, compelling and uplifting, Long Walk to Freedom is the exhilarating story of an epic life; a story of hardship, resilience and ultimate triumph told with the clarity and eloquence of a born leader.
Includes bibliographical references
Keywords: Nelson Mandela